(untitled) (Research, Society and Development, 2022)
The emergence of the knowledge economy raises the importance of identifying elements that may favor overcoming barriers related to the capacity of regions to generate and disseminate commercially relevant knowledge. The aim of this article is to examine how the literature uses the Knowledge Spillover Theory of Entrepreneurship (KSTE) to discuss the link between technological knowledge and technology-based entrepreneurship. The KSTE was formulated in the last 10 years, and since then, its diffusion has taken place among researchers in the world scientific community and is present in several research fields. The results indicate that KSTE has been adopted as a foundation that explains the relationship between two phenomena, technological entrepreneurship, and knowledge, especially from works published from 2013 onwards. It is also observed that research in this field has grown rapidly, associating it with entrepreneurial and innovative ecosystems. This study has academic relevance and innovates by identifying the main themes of the literature in the light of the Theory of Entrepreneurship through Knowledge Overflow, complementing previous research in the area and indicating a new research direction.